Analisis Unjuk Kerja Turbin Ulir Archimedes Satu Sudu dengan Variasi Head - Gad Gunawan; Cloudiandy Mukti Kimana; Doddy Suanggana; Alfian Djafar (Universitas Islam Raden Rahmat, Malang, 2024)
An alternative solution that answers the problem of fossil energy is the use of renewable energy. Hydropower is one of the renewable energies that is widely used in the world. One kind of turbines that is suitable for application in low head conditions is the Archimedes Screw Turbine. This research aims to test the performance of Archimedes screw turbines on several heads, namely 300 mm, 500 mm and 700 mm heads. The number of blade in this turbine is one. The method used is experimentation, which is carried out in the laboratory on a designed testing installation. In this experiment, the highest power obtained at a 700 mm head was 6,407 Watts and the greatest efficiency was 26.59% at a 500 mm head variation. This shows that the performance of a turbine depends on its operating conditions.